Impact of Technology on the Financial Performance of Indian Commercial Banks - Jayalakshmi, S; Mythili, R (Ushus Journal of Business Management, 2024)
The banks’ freedom to choose their capital structure is restricted by the capital adequacy rules. The implementation of the capital adequacy ratio may have a detrimental effect on the banks’ profitability. Since debt repayment imposes restraint on managers’ behaviour, It has been argued that when capital ratios are larger, agency costs between managers and shareholders typically increase.. However, the improved monitoring required by the capital adequacy rules and the larger surplus brought about by a positive bank-borrower relationship will have a favourable effect on the banks’ profitability. Indian banking. stated that in terms of cost and profit efficiencies, Indian public sector banks were more effective than private and foreign banks. The use of technology enabled banks to create their own websites that their clients may view from the comfort of their homes or offices using web browsers.